Introduction: Social Reproduction and the Challenge to Legal Studies - Rigo, Enrica; Alessandrini, Donatella (feminists@law, 2023)
Enrica Rigo and Donatella Alessandrini introduce the short contributions from feminists who took part in the international workshop on Law and Social Reproduction: The Misconceived Value of Care which was held at Roma Tre University, Rome on 4-5 May 2023. Building on crosscutting approaches from different disciplines, the workshop explored the potential of social reproduction for developing critical legal approaches capable of addressing the challenges posed by the diversity of feminist struggles.